Multi-field driven thermochromic films and preparation of multi-color patterns. Issue 13 (21st October 2022) - Zheng, Jiasong; He, Zemin; Li, Chunsheng; Miao, Zongcheng; Wang, Dong; Luan, Yi; Li, Yuzhan; Zhao, Yuzhen
ABSTRACT: In this paper, multi-field driven thermochromic films (TCF) were successfully prepared firstly. The upper layer is polymer-dispersed liquid crystal (PDLC) film prepared by polymerisation-induced phase separation (PIPS), and the lower layer is thermochromic liquid crystal microcapsule film prepared by centrifugal spin-coating method. The effects of diluent content, liquid crystal content and spin coating speed on the electro-optical properties and morphology of the thermochromic films were investigated by three sets of experiments secondly. Finally, multi-field driven multi-colour patterns were successfully prepared by film formation on conductive glass and flexible conductive films. Thermal ageing tests proved that the thermochromic films possess better service life, which provides a possibility for the wide application of liquid crystal films. GRAPHICAL ABSTRACT: uf0001